USAHA BANK SEBAGAI LEMBAGA PENYALUR KREDIT KEPADA MASYARAKAT - Dharu Triasih (Humani (Hukum dan Masyarakat Madani), 2016)
Kegiatan bank secara umum dapat disimpulkan sebagai kegiatan untuk menyerap dana dari masyarakat dan menyalurkan kembali kepada masyarakat melalui pembiayaan salah satunya berupa kredit oleh lembaga perbankan. Kondisi pada saat ini di mana  orang yang membutuhkan kredit (calon nasabah debitur) masih jauh lebih banyak dari jumlah kredit yang dapat ditawarkan oleh perbankan, maka bank lebih memilih untuk hanya melayani calon-calon nasabah yang bersedia menerima  klausul - klausul yang sudah tersedia tanpa perubahan sebagaimana yang telah disusun oleh  kantor pusat bank tersebut, dari pada harus melayani calon nasabah debitur yang menginginkan perjanjian kredit dengan klausul - klausul yang dirundingkan. Perkembangan keadaan menjadi seperti ini lebih-lebih lagi karena ditunjang oleh kenyataan bahwa nasabah-nasabah debitur yang kebanyakan terdiri dari pengusaha-pengusaha kecil atau golongan ekonomi lemah itu sering tidak merasa perlu untuk berpayah-payah merundingkan klausul-klausul perjanjian kredit dari kredit yang diterimanya. Hubungan hukum antara bank dengan nasabah adalah hubungan Hukum Perdata yang lahir melalui perjanjian, sehingga berlaku ketentuan KUHPerdata dan peraturan perundang-undangan yang berlaku di bidang perbankan. Dalam kegiatan usahanya, bank selalu berusaha memberikan perlindungan hukum kepada nasabah secara preventif dan represif, meliputi perlindungan kepentingan fisik dan ekonomis nasabah. The activities of banks in general can be summed up as an activity to absorb funds from the public and to channel back to the community through one form of credit financing by banking institutions. The conditions at this time where people are in need of credit (prospective debtor) is still much higher than the amount of credit that can be offered by the banks, then the banks would prefer to only serve prospective clients who are willing to accept the clause - a clause that has been available without a change as it has been drawn up by the bank's headquarters, of the debtor must serve prospective customers who want a credit agreement with a clause - a clause negotiated. Development of the situation being like this the more so because it is supported by the fact that the clients of the debtor which mostly consists of small entrepreneurs or economically weak groups that often do not feel the need to toil negotiate clauses of a credit agreement of the credit received.Legal relationship between the bank and its customers is a civil law relationship that was born through an agreement, so that the applicable provisions of the Civil Code and the laws in force in the field of banking. In the normal course of business, the bank is always trying to give legal protection to customers, preventive and repressive, covering physical and economic protection of the interests of customers.The activities of banks in general can be summed up as an activity to absorb funds from the public and to channel back to the community through one form of credit financing by banking institutions. The conditions at this time where people are in need of credit (prospective debtor) is still much higher than the amount of credit that can be offered by the banks, then the banks would prefer to only serve prospective clients who are willing to accept the clause - a clause that has been available without a change as it has been drawn up by the bank's headquarters, of the debtor must serve prospective customers who want a credit agreement with a clause - a clause negotiated. Development of the situation being like this the more so because it is supported by the fact that the clients of the debtor which mostly consists of small entrepreneurs or economically weak groups that often do not feel the need to toil negotiate clauses of a credit agreement of the credit received.Legal relationship between the bank and its customers is a civil law relationship that was born through an agreement, so that the applicable provisions of the Civil Code and the laws in force in the field of banking. In the normal course of business, the bank is always trying to give legal protection to customers, preventive and repressive, covering physical and economic protection of the interests of customers.